2008
DOI: 10.1073/pnas.0707654105
|View full text |Cite
|
Sign up to set email alerts
|

Circulation and long-term fate of functionalized, biocompatible single-walled carbon nanotubes in mice probed by Raman spectroscopy

Abstract: Carbon nanotubes are promising new materials for molecular delivery in biological systems. The long-term fate of nanotubes intravenously injected into animals in vivo is currently unknown, an issue critical to potential clinical applications of these materials. Here, using the intrinsic Raman spectroscopic signatures of singlewalled carbon nanotubes (SWNTs), we measured the blood circulation of intravenously injected SWNTs and detect SWNTs in various organs and tissues of mice ex vivo over a period of three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
897
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 1,047 publications
(943 citation statements)
references
References 38 publications
43
897
2
1
Order By: Relevance
“…59 69) More importantly, the biodegraded SWNTs did not elicit a proinflammatory response in mice after pharyngeal aspiration, which was observed in previous studies for SWNTs 75) and MWNTs. 76) With regard to SWNT excretion, Liu et al used Raman microscopy to analyze the various organs of mice for up to 3 months after intravenous injection of SWNTs coated with PEG-PL conjugates.…”
Section: Safetysupporting
confidence: 58%
See 3 more Smart Citations
“…59 69) More importantly, the biodegraded SWNTs did not elicit a proinflammatory response in mice after pharyngeal aspiration, which was observed in previous studies for SWNTs 75) and MWNTs. 76) With regard to SWNT excretion, Liu et al used Raman microscopy to analyze the various organs of mice for up to 3 months after intravenous injection of SWNTs coated with PEG-PL conjugates.…”
Section: Safetysupporting
confidence: 58%
“…51) In vivo studies were also performed with (6,5)-SWNTs on subcutaneous tumor-bearing mice. By detecting the intrinsic Raman G band of SWTNs after intravenous administration, 59) the blood circulation half-life of (6,5)-SWNTs coated with C 18 -PMH-mPEG was determined to be 23.95±1.49 h. 51) The authors also reported that the half-life of SWNTs was extendable up to 1 d with a branched PEG (7000) chain-PL conjugate. 59) The tumor uptake of (6,5)-SWNTs was ca.…”
Section: Optical Properties Of Swntsmentioning
confidence: 93%
See 2 more Smart Citations
“…Amphiphilic polymers with a low critical micelle concentration (CMC), e.g., Poloxamer ® , Poloxamine ® and lipid-PEG copolymer, can form a stable coating layer around hydrophobic cores [98,114,119]. Amphiphilic polymer coated carbon nanotubes, polystyrene beads, quantum dots, and superparamagnetic iron oxide nanoparticles have been used in in vitro and in vivo applications [17,97,98,114,120,121]. This coating can be generalized for many hydrophobic nanocrystals because it does not rely on the reactivity of the crystal surface [98].…”
Section: Nanoparticle-based Mri and Mr/pet Imaging Contrast Agentsmentioning
confidence: 99%